Primary Retrovesical Hydatid Cyst causing Acute Urinary Retention in a Young Patient : A Rare Presentation - Lomesh A. Kapadnis; Vikash Kumar; Ajit S. Sawant; Gaurav V. Kasat; Ashwin S. Tamhankar (International Journal of Anatomy Radiology and Surgery, 2016)
Retrovesical cysts are very rare. Definitive preoperative diagnosis is difficult in many cases. Hydatid cyst can present as a retrovescial cyst, which can cause a diagnostic dilemma. We present a case of primary retrovesical hydatid cyst mimicking a prostatic utricle cyst, presenting as acute urinary retention in a 29 year old young male patient. Definitive pre-operative diagnosis was difficult even with detailed imaging studies. Hence, exploratory laparotomy was done and diagnosis was suggested intra-operatively by the presence of slimy germinal layer and a daughter cyst and confirmed by histopathological examination. Hydatid disease is a zoonotic disease caused due to larvae of Ecchinococcus granulosus. Humans are the accidental intermediate hosts. Urogenital system is involved in 2.15% and in that, kidney is most commonly involved organ. As such, the retrovesical location is involved very rarely. Hence, retrovesical cysts are rare and hydatid cyst should be kept as differential diagnosis in mind while treating such cysts